Implementation of Problem-Based Learning Model in Class V of MIN Kota Bima - Irma Indriani (FASHLUNA, 2025)
This study aims to examine the implementation of the Problem-Based Learning (PBL) model in elementary school education. PBL is an approach that places students at the center of learning by emphasizing real-world problem-solving as a means to develop critical thinking skills, collaboration, and active engagement in the learning process. This research uses a qualitative approach with a case study design at MIN Kota Bima, involving two teachers and 30 students from grades V. Data were collected through in-depth interviews with teachers, direct observation of learning activities, and document analysis of lesson plans (RPP) as well as student work. The findings indicate that the implementation of PBL provides significant benefits, such as enhancing students' critical thinking and collaboration skills, as well as making learning more meaningful and relevant. However, there are several challenges in implementing PBL, including limited resources, teacher readiness, and the limited time available in the curriculum. The study concludes that although PBL holds great potential to improve the quality of learning in elementary schools, further efforts are needed to prepare teachers and provide supporting facilities for the successful implementation of this model.